2011
DOI: 10.1164/rccm.201107-1173oc
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Fragmentation Induces Cognitive Deficits Via Nicotinamide Adenine Dinucleotide Phosphate Oxidase–dependent Pathways in Mouse

Abstract: Rationale: Sleep fragmentation (SF) is one of the major characteristics of sleep apnea, and has been implicated in its morbid consequences, which encompass excessive daytime sleepiness and neurocognitive impairments. We hypothesized that absence of nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity is neuroprotective in SF-induced cognitive impairments. Objectives: To examine whether increased NADPH oxidase activity may play a role in SF-induced central nervous system dysfunction. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 158 publications
(149 citation statements)
references
References 79 publications
(92 reference statements)
9
138
1
1
Order By: Relevance
“…[29][30][31][32][33] Both intermittent hypoxia and increased oxidative stress are hallmark characteristics of OSA, 34 and the degree of oxidative stress associated with OSA has emerged as an important determinant of cognitive dysfunction in both animal models and in children. [35][36][37] A unique and intriguing observation in the present study involves the differential and predictable changes in urinary neurotransmitters in children with OSA and without evidence of neurocognitive dysfunction. In this context, the patterns of overnight changes in levels of three neurotransmitters, namely GABA, taurine, and PEA, allowed accurate prediction of cognitive defi cits in this small cohort ( Fig 2 ).…”
Section: Discussionmentioning
confidence: 80%
“…[29][30][31][32][33] Both intermittent hypoxia and increased oxidative stress are hallmark characteristics of OSA, 34 and the degree of oxidative stress associated with OSA has emerged as an important determinant of cognitive dysfunction in both animal models and in children. [35][36][37] A unique and intriguing observation in the present study involves the differential and predictable changes in urinary neurotransmitters in children with OSA and without evidence of neurocognitive dysfunction. In this context, the patterns of overnight changes in levels of three neurotransmitters, namely GABA, taurine, and PEA, allowed accurate prediction of cognitive defi cits in this small cohort ( Fig 2 ).…”
Section: Discussionmentioning
confidence: 80%
“…Physiological data were continuously acquired for 24 h using Dataquest ART acquisition software (version 3.1, DSI), at a sampling rate of 500 Hz. Data were first scored automatically using SleepSign software (Kissei Comtec) (11,34,44), and records were then visually confirmed or corrected as needed by an investigator who was blinded to the experimental condition.…”
Section: General Experimental Set Upmentioning
confidence: 99%
“…In this mode, the sweeper requires around 9 s to sweep the floor of the cage one way. When it reaches the end of the cage, a relay engages the timer to pause for 2 min before enabling the sweeper to move in the opposite direction (34,44). Between the two intervals, the animal remained undisturbed.…”
Section: Sleep Fragmentationmentioning
confidence: 99%
“…15,26,27 3-mo-old WT and gp91 phox-/Y mice were exposed to either SF or normal sleep conditions (SC; the SF cage was used but the sweeper remained immobile). To induce moderate to severe SF, we chose a 2-min interval between each sweep, implemented during the light period (7:00 am-7:00 pm).…”
Section: Sleep Fragmentation (Sf) Paradigm and Tc1 Tumor Modelmentioning
confidence: 99%
“…14 In a series of studies exploring some of the deleterious consequences of SF, we identified the presence of increased Nox2-derived ROS and oxidative stress as major pathophysiological determinants of end-organ morbidity. [15][16][17] Based on such findings and the promoting effects of SF on tumor growth and invasion, 3 we hypothesized that genetic ablation of Nox2 would potentially elucidate the role of this important source of ROS in the oncogenic processes modulated by SF, and potentially abolish the pro-tumorigenic effects of SF.…”
Section: Introductionmentioning
confidence: 99%